Strategi Optimasi Digital Marketing dalam Upaya Meningkatkan Omset Penjualan Ayam Geprek Sambal Ijo Dua Putri pada Platform E-Commerce - Dini Yani; Dexi Triadinda; Zenita Apriani; Shandikha Arya Yudha Rahman (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
By using Digital Marketing, business actors are expected to be able to increase sales well gradually. Ayam Geprek Sambal Ijo Dua Putri, which has been established since 2018 and owned by Mrs. Onik, is an MSME that has grown and developed its business. Strategically located on Jl. HS. Ronggo Waluyo, Puseur Jaya, Telukjambe Timur, Karawang, this stall offers geprek chicken with delicious green chili sauce and affordable prices. In facing the digital era, Mrs. Onik, as the owner of Ayam Geprek Sambal Ijo Dua Putri, has wisely recognized the potential of online marketing as the key to the success of her business. With a daily turnover of 4 million rupiah through offline channels, as well as their success in collaborating with Shopee Food and Grab Food, the next step taken is to expand their presence in the digital realm. Marketing through social media platforms, especially Instagram, and the use of banners as a strategy to attract consumers, are considered strategic steps that will allow them to reach more potential customers. The selection of Ayam Geprek Sambal Ijo Dua Putri as the focus of the research is very appropriate because of its strategic location, right on the side of the road, making it the main choice for many people passing by.